PEMBERIAN KURMA AJWA TERHADAP KENAIKAN KADAR HEMOGLOBIN PADA IBU HAMIL TRIMESTER III - Titin Yulianti; Iis Tri Utami (Universitas Fort De Kock, 2021)
ABSTRACT Anemia on pregnant women when the hemoglobin level is below 11 gr/dL. Dates are one of the non-pharmacological therapies in the treatment of anemia. The iron content, protein, carbohydrate and fat content in dates can help the process of hemoglobin synthesis. The research objective was to determine the effect of giving Ajwa dates to increase of hemoglobin levels on the third trimester of pregnant women at the inpatient community health center of Tanjung Mas Makmur 2021. The research method used Quasi Experiment with non-equivalent control group pretest and posttest design. The sample studied were pregnant women with mild anemia as many as 36 respondents. The experimental group was given 100 grams of ajwa dates and the control group was given 1 Fe tablet for 14 days. Bivariate analysis used the T test (Independent Sample test). The results of univariate analysis showed that in the case group the average hemoglobin level before giving Ajwa dates was 10.32 and after giving Ajwa dates was 10.79 gr / dL, in the control group the average hemoglobin level before giving Fe tablets was 10.00 gr / dL and after giving Fe tablet was 10.26 gr / dL. Bivariate analysis showed that there was an effect of giving Ajwa dates to increase of hemoglobin level on the third trimester of pregnant women at the inpatient community health center of Tanjung Mas Makmur 2020 (p value 0.003 <0.05). It is expected that pregnant women should consume dates and fulfill nutrition with a variety of foods rich in iron in accordance with local wisdom.Keywords : Ajwa Dates, Hemoglobin Levels, Pregnant Women ABSTRAK Anemia pada ibu hamil bila kadar hemoglobin dibawah 11gr/dL. Kurma merupakan salah satu terapi nonfarmakologi dalam pengobatan anemia. Kadar zat besi, kandungan protein, karbohidrat dan lemak pada kurma dapat membantu proses sintesis hemoglobin. Tujuan penelitian untuk mengetahui pengaruh pemberian kurma ajwa terhadap kenaikan kadar hemoglobin pada ibu hamil Trimester III di Wilayah Kerja Puskesmas Rawat Inap Tanjung Mas Makmur Tahun 2021. Metode penelitian ini menggunakan Quasi Eksperimen dengan desain non equivalent control group pretest and posttest. Sampel yang diteliti yaitu ibu hamil dengan anemia ringan sebanyak 36 responden. Kelompok eksperimen diberikan 100 gram kurma ajwa dan kelompok kontrol diberikan 1 tablet Fe selama 14 hari. Analisis bivariat menggunakan Uji T (Independent Sampel test). Hasil analisis univariat diketahui bahwa rata-rata kadar hemoglobin pada kelompok kasus sebelum diberikan kurma ajwa adalah 10,32 gr/dL dan sesudah pemberian kurma ajwa adalah 10,79 gr/dL, rata-rata kadar hemoglobin pada kelompok kontrol sebelum diberikan tablet fe adalah 10,00 gr/dL dan sesudah pemberian tablet Fe adalah 10,26 gr/dL. Analisis bivariat menunjukkan bahwa ada pengaruh pemberian kurma terhadap kenaikan kadar hemoglobin pada ibu hamil TM III (p value 0,003<0,05). Diharapkan bagi ibu hamil agar mengonsumsi kurma dan makan makanan yang beraneka ragam yang kaya akan zat besi sesuai kearifan lokal.Kata Kunci : Kurma Ajwa, Kadar Hemoglobin, Ibu Hamil